The indirect impacts of management support and commitment on knowledge management systems (KMS) adoption: evidence from Malaysian Technology Industries - Aman, Fadhilah; Aitken, Ashley (Academic Journals, 2011)
The study investigates the impacts of management support and commitment on the adoption of knowledge management systems (KMS) in Malaysian technology industries. By analysing data from a survey of 108 managers across the Malaysian technology industries, the study contributes to the KMS adoption literature by empirically establishing the indirect impacts of organisations’ management support and commitment through the mediations of other organisational elements. First of all, the results suggest that the effects of management support and commitment are only indirect through the mediation of other variables, namely knowledge classification and knowledge sharing culture. Moreover, knowledge classification has a positive influence on perceived benefits, which is a determinant of KMS adoption. Second, even though management support and commitment has a positive impact on rewards and incentives, and policy and procedures, the findings indicate that these organisational elements did not have any influence on KMS adoption. However, policies and procedures did influence perceived ease of use, which is a determinant of perceived benefits. The theoretical and practical implications of these findings are discussed.